Resource use associated with type 2 diabetes in Africa, the Middle East, South Asia, Eurasia and Turkey: results from the International Diabetes Management Practice Study (IDMPS) - Gagliardino, Juan Jose (2017)
Type 2 diabetes (T2D) and its complications form a global healthcare burden but the exact impact in some geographical regions is still not well documented. We describe the healthcare resource usage (HRU) associated with T2D in Africa, the Middle East, South Asia, Eurasia and Turkey.